Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/ajg.2011.161
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-122 as a Biomarker of Necroinflammation in Patients With Chronic Hepatitis C Virus Infection

Abstract: OBJECTIVES: The liver contains large amounts of microRNA-122 (miR-122), whereas other tissues contain only marginal amounts of this miRNA. MicroRNAs have also been found to circulate in the blood in a cell free form; their potential as readily accessible disease markers is currently evaluated. Here we investigated if the serum levels of miR-122 might be useful as disease parameter in patients with chronic hepatitis C virus (HCV) infection.METHODS: RNA was extracted from sera of patients with chronic HCV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
167
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(191 citation statements)
references
References 33 publications
21
167
2
1
Order By: Relevance
“…Recent studies convincingly showed that miRNAs stably present in human serum or plasma samples by the carriers of exosomes or argonaute2 (Ago2) complex (16,17), and may be used as diagnostic markers in several cancers (18,19). Serum miR-122 has been implicated as a potential biomarker in drug-, alcohol-, hepatitis B virus-, or HCV-related liver diseases and HCC (20)(21)(22)(23)(24). However, the role of serum miR-122 in the management of CHC remains largely unknown and deserves further investigations.…”
mentioning
confidence: 99%
“…Recent studies convincingly showed that miRNAs stably present in human serum or plasma samples by the carriers of exosomes or argonaute2 (Ago2) complex (16,17), and may be used as diagnostic markers in several cancers (18,19). Serum miR-122 has been implicated as a potential biomarker in drug-, alcohol-, hepatitis B virus-, or HCV-related liver diseases and HCC (20)(21)(22)(23)(24). However, the role of serum miR-122 in the management of CHC remains largely unknown and deserves further investigations.…”
mentioning
confidence: 99%
“…40,44,45 Serum/plasma levels of miR-122 correlate with hepatic necro-inflammation, liver damage, cell death and increased aminotransferase levels in acute and chronic liver diseases. 44,[46][47][48][49] Interestingly, hepatic and circulating miR-122 levels do not correlate in NAFLD 14,39,[50][51][52][53][54][55] or viral hepatitis 41,47,49,56 although both have been statistically associated with various measures of disease severity in these studies. Together these studies show that miR-122 may play a role in most liver diseases.…”
Section: Microrna-122mentioning
confidence: 62%
“…58 MiRs are likely to have a role in viral hepatitis as cellular miRs play an important role in viral pathogenesis. 59 The level of plasma miR-122 exhibits an excellent correlation with the necroinflammatory activity of HBV 41 and HCV 47 infections. Altered miR expressions during virus infection include host miRs that target virus sequences and host genes to modulate and influence viral replication.…”
Section: Viral Hepatitismentioning
confidence: 99%
“…As well as in sera or plasma from humans and rodents upon toxic liver injury [20][21][22]. Moreover, circulating miR-122 has been proposed as a marker of infl ammation in patients with chronic hepatitis C viral infection [23].…”
Section: Micrornasmentioning
confidence: 99%
“…(miRNAs, miRs) are small (18)(19)(20)(21)(22)(23)(24)(25) ribonucleotides) non-coding RNAs which function in transcriptional and post-transcriptional regulation of gene expression [11]. Circulating miRs are,in large part, derived from cells with damaged plasma membrane [12] and circulate in the blood freely and in a relatively stable form [13,14].…”
Section: Micrornasmentioning
confidence: 99%